5-aminolevulinic acid-conjugated gold nanoparticles for photodynamic therapy of cancer. (December 2008) - Khaing Oo, Maung Kyaw; Yang, Xiaochuan; Du, Henry; Wang, Hongjun
Background: Effective delivery of photosensitizer to target tumor cells that causes minimal damage to healthy cells is an important requirement in photodynamic therapy of cancer.Aim: We aimed to use biocompatible gold nanoparticles as a vehicle to deliver 5-aminolevulinic (5-ALA) acid for selective and efficient photodynamic therapy.Results: Protoporphyrin IX accumulated preferentially in fibrosarcoma tumor cells treated with 5-ALA-conjugated nanoparticles while yielding significantly higher reactive oxygen species compared with that with 5-ALA. The elevation of reactive oxygen species resulted in 50% more cytotoxicity to tumor cells than that of 5-ALA alone. Selective destruction of tumor cells was also achieved using 5-ALA-conjugated nanoparticles in co-culture with dermal fibroblasts.Conclusions: 5-ALA-conjugated nanoparticles offer a new modality for selective and efficient destruction of tumor cells, with minimal damage to fibroblasts in the 5-ALA-photodynamic therapy.